Evaluation of the post-labioplasty result according to the comprehensive assessment performed by Indonesian Cleft Center team - Zainul Abidin, Siti Nur Nabihah; Astuti, Ida Ayu; Arumsari, Asri (Padjadjaran Journal of Dentistry, 2015)
Introduction: Labioplasty is a surgical approach to reconstructs and repairs the cleft lip defect. The main purpose of this study is to observe the performance result of labioplasty through out the period of January till December 2007 according to the comprehensive assessment performed by Indonesian Cleft Center Team. Other purpose is to determine the least and the most complicated structure to be reconstructed in labioplasty. Apart from that, types of secondary reconstructive surgery, how many patients require and implement this secondary surgery are determined in this study. Methods: The method used for this study was descriptive retrospective which in the sample are post-labioplasty patients that came for assessment. With astounding years of experience, Indonesian Cleft Center Team is expected able to handle every case judiciously regarding its clinical severity. Results: Result shows that the performance result of labioplasty does not necessarily coincided with the severity of the cases. The most complicated structure to be reconstructed in labioplasty is Cupid’s bow whilst the least complicated are the thickness of vermilion and avoidance to create cicatrix. Conclusion: Type of secondary reconstructive indicated for the patient to repair the remaining deformities are secondary lip repair, rhinoplasty, fistula closure and bone graft. The amount of patient that is indicated for it is in total 25 patients and only 1 patient implemented the surgery.